The Riddle of Style Changes in the Visual Arts after Interference with the Right Brain - Blanke, Olaf; Pasqualini, Isabella (Frontiers in Human Neuroscience, 2012)
What is visual art? What are paintings? What are films? Although innumerous answers have been proposed to these questions, we here analyze the paintings and films of several visual artists, who suffered from a well-defined neuropsychological deficit, visuo-spatial hemineglect, following vascular stroke to the right brain. We focus our analysis in particular on the oeuvre of Lovis Corinth and Luchino Visconti and point out aspects of their post-stroke paintings and films (that differ from their pre-stroke work) and argue that these changes may be associated with visuo-spatial hemineglect. We discuss how the neuropsychological investigation of visual artists may allow us to investigate the relationship between brain and art.